Exploring the potential of bottle gourd (Lagenaria siceraria) flour as a fat mimetic in biscuits with improved physicochemical and nutritional characteristics and anti-diabetic properties - Ghufran Saeed, Syed Muhammad; Ali, Syed Arsalan; Ali, Rashida; Sayeed, Syed Asad; Mobin, Lubna (Italian Journal of Food Science, 2022)
Bottle gourd (Lagenaria siceraria) is a naturally rich source of several phytochemicals that play a vital role in the prevention of diseases. In the present study, the effect of bottle gourd flour (BGF) as a fat mimetic in biscuits at different concentrations (10, 15, 20, 25, and 50% w/w) was explored. Rheological properties, the microstructure of dough, bioactive compounds, anti-diabetic potential, storage stability, and the nutritional, physical, and sensory properties of samples were investigated. The addition of BGF in wheat flour (WF) showed increased water absorption (58.70–72.43%) and reduced dough stability time (11.71–5.01 min). Trough (1165.11–1096.10 Torque) and set back viscosities (471.21–448.09 Torque) decreased significantly (P ≤ 0.05) with the increased level of BGF in WF. Furthermore, gluten content was also reduced. The baking process decreased the IC50 values, although total phenol content and total flavonoid content decreased. Shelf life study of 2 months revealed no significant (P ≤ 0.05) difference in bioactive compounds, and alpha-amylase inhibition activity of fat-replaced biscuits. Moreover, the anti-hyperglycemic activity of BGF-WF biscuits in human subjects also showed positive results. The percentage increase in both peroxide value (0.2–2.87 milliequivalent O2/kg of fat) and free fatty acid (0.1–0.9%) during storage was significantly (P ≤ 0.05) lower than control biscuits (0.9–5.53 mill-equivalent O2/kg of fat and 0.2–1.1%), which correlates to the enhanced activity of bioactive compounds in BGF-WF biscuits, which in turn relates to decreasing the rate of oxidation. The crude fiber and protein contents of BGF-WF biscuits were improved from 0.21 to 17.30% and 11.20 to 18.70%, respectively. Sensory and textural performance exhibited that the biscuits were acceptable after fat replacement of up to 15% BGF. Based on this study, BGF may be suggested as an excellent natural fat replacer to be used in nutraceuticals and functional foods.